Spider mite infestations reduce Bacillus thuringiensis toxin concentration in corn leaves and predators avoid spider mites that have fed on Bacillus thuringiensis corn. (17th March 2014) - Prager, S.M.; Martini, X.; Guvvala, H.; Nansen, C.; Lundgren, J.
Abstract Perceived benefits of insecticidal transgenic crops include reduced usage of broad‐based insecticides, and therefore lower risk to non‐target organisms. Numerous studies have documented low or no direct toxicity of Bacillus thuringiensis (Bt)‐derived toxins against non‐target organisms, but there has been less research on (a) effects of secondary pest infestations on Bt expressing in crops and (b) behavioural responses by predators feeding on host arthropods from Bt crops – both topics are investigated in this study. We quantified predation by the obligate spider mite predator Phytoseiulus persimilis of carmine spider mites (Tetranychus cinnabarinus), reared on Bt or non‐Bt corn (Zea mays). Both no‐choice and two‐choice studies were conducted. In addition, we quantified toxin levels in corn leaves with/without spider mite infestation. Under no‐choice conditions, P. persimilis consumed non‐Bt spider mites at a faster rate than Bt spider mites. Under two‐choice conditions, P. persimilis spent more time in the vicinity of non‐Bt spider mites than near Bt spider mites. Corn infested with spider mites exhibited lower toxin levels than non‐infested plants. These results suggest potentially complex interactions among non‐target herbivores, their natural enemies and Bt crops.